2006
DOI: 10.1007/s00280-006-0307-5
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes in bladders of patients submitted to ifosfamide chemotherapy even with mesna prophylaxis

Abstract: The standard protocol used for prevention of IFS-induced HC with three doses of mesna does not completely prevent bladder damage. The histopathological criteria used in this study for observation of inflammatory events allowed staging the intensity of IFS-induced urothelial and mucosal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…On the other hand, etoricoxib did not exhibit this side eVect even with higher dose. It was shown that signiWcative degrees of bladder damage in patients submitted to ifosfamide-based chemotherapy even with the classical prevention with three doses of mesna and that dexamethasone added to mesna was more eYcient in preventing IFS-induced HC when mesna was used alone in rats (Vieira et al 2003;Lima et al 2007). This was similar with our results where we added COX-2 inhibitors to mesna.…”
Section: Experimental Groups Urothelial Cells Sub-epithelial Cells Pasupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, etoricoxib did not exhibit this side eVect even with higher dose. It was shown that signiWcative degrees of bladder damage in patients submitted to ifosfamide-based chemotherapy even with the classical prevention with three doses of mesna and that dexamethasone added to mesna was more eYcient in preventing IFS-induced HC when mesna was used alone in rats (Vieira et al 2003;Lima et al 2007). This was similar with our results where we added COX-2 inhibitors to mesna.…”
Section: Experimental Groups Urothelial Cells Sub-epithelial Cells Pasupporting
confidence: 93%
“…However, despite positive results after the prophylactic use of mesna for preventing HC, bladder protection is not always achieved, particularly when a lesion has already been established (Shulman 1993). The occurrence of cystitis despite Mesna was observed either experimentally (Vieira et al 2003) or clinically (Lima et al 2007). These facts enhance the importance of studies that investigate the mechanisms involved in bladder lesions resulting from alkylating agent therapies.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, despite positive results after the prophylactic use of mesna for preventing HC, bladder protection is not always achieved, particularly when a lesion has already been established [6]. The occurrence of cystitis despite mesna was observed both experimentally [7] and clinically [8]. These facts enhance the importance of studies that investigate the mechanisms involved in bladder lesions resulting from alkylating agent therapies.…”
Section: Introductionmentioning
confidence: 65%
“…[29][30][31] Mucosal lesions, such as edema or hemorrhage, will occur and mucosal permeability will increase after CYP treatment. 32 It is suspected that nitric oxide release, 33 inflammation and hyperactivity 34 after CYP treatment is associated with the disruption of mucosa. Bladder HA instillation helps prevent mucosa from pathological damages.…”
Section: Discussionmentioning
confidence: 99%